1992
DOI: 10.1093/jn/122.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soluble Fiber and Cholesterol Affect Serum Cholesterol Concentration, Hepatic Portal Venous Short-Chain Fatty Acid Concentrations and Fecal Sterol Excretion in Rats

Abstract: Sprague-Dawley rats were fed diets containing 7.5% dietary fiber as cellulose (control), pectin, psyllium or oat bran with or without 0.3% added cholesterol for 3 wk. Among rats fed cholesterol, liver total lipid and cholesterol concentrations were significantly lower in groups fed pectin, psyllium and oat bran compared with cellulose-fed controls. Cholesterol feeding resulted in significantly greater liver cholesterol in rats fed cellulose, psyllium and oat bran but not in those fed pectin. Among rats fed cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 13 publications
2
50
0
7
Order By: Relevance
“…It is reported 5,21) that the propionate prevents the synthesis of a cholesterol because it inhibits the HMG CoA synthase, the HMG CoA reductase and the acetyl CoA synthetase activities. There are some conflicts between propionate concentration and choresterol synthesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported 5,21) that the propionate prevents the synthesis of a cholesterol because it inhibits the HMG CoA synthase, the HMG CoA reductase and the acetyl CoA synthetase activities. There are some conflicts between propionate concentration and choresterol synthesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The hypocholesterolemic effects of psyllium (Olson et al 1997), guar gum (Todd et al 1990) and oat bran (Ripsin et al 1992) are well documented by meta -analyses. Animal studies have consistently shown that fibres that reduce plasma cholesterol increase neutral sterol or bile acid excretion (Illman and Topping 1985;Kritchevsky 1988;Arjmandi et al 1992). Many large epidemiological studies such as Nurses' Health Study and Scottish Heart Health Study have demonstrated a reduced risk for CHD in both men and women who consume higher amounts of dietary fibre (Anderson and Hanna 1999;Todd et al 1999;Wolk et al 1999).…”
Section: Role Of Dietary Fibre In Prevention Of Cardiovascular Diseasementioning
confidence: 99%
“…Já os resultados apresentados concordaram com os resultados de ROSA et al [33,34] e SHINNICK et al [35], de fibras mistas de feijões e farelo de aveia, respectivamente. Para as dietas com pectina os resultados estão de acordo com os estudos de ARJMANDI et al [7,8] …”
Section: -Consumo Alimentar E Ganho De Pesounclassified
“…Este comportamento pode ser atribuído ao caráter hidrofílico de certas fibras, como as pectinas e as gomas, que fazem com que a taxa de esvaziamento gástrico seja mais lenta, aumentando a saciedade, e conseqüentemente reduzindo a ingestão de alimentos [15]. O presente trabalho promoveu redução no ganho de peso dos animais alimentados com as dietas acrescidas de pectina em relação à dieta controle, concordando com os trabalhos de ARJMANDI et al [7,8] que pesquisaram pectina, psyllium e farelo de aveia. Porém, discorda dos resultados apresentados por AL-OTHMAN et al [2]; JIMENEZ-VERGARA et al [21] e YAMADA et al [40], os quais pesquisaram a goma arábica, pectina e a goma guar, respectivamente.…”
Section: -Consumo Alimentar E Ganho De Pesounclassified
See 1 more Smart Citation